Knowledge and Attitudes of Young Women about Early Detection of Breast Cancer through Breast Self-Examination (BSE) - Siska Farlina; Muliani Muliani; Lili Suryani; Sarliana Sarliana; Nurfatimah Nufatimah; Sumiaty Sumiaty (Poltekkes Kemenkes Palu, 2023)
Background: Breast cancer is the most common cancer in women, is a malignant tumor that grows in breast tissue. Data from the Health Office of Central Sulawesi, the percentage of tumors/lumps in 2018 was 0.18%. in 2019 0.2%. in 2020 increased 0.4%. One of the efforts to detect breast cancer early is BSE. Purpose To know the effect of health education on the level of knowledge and attitudes of young women about early detection of breast cancer through Breast Self Examination in the Huntap Tondo area. Methods The type of research is quasi-experimental with one group pretest-posttest design. The research sample was young women aged 14-19 years totaling 55 respondents taken by purposive sampling. The research instrument used a standardized questionnaire with a total of 20 knowledge questions and 10 attitudes. The research was conducted on 2-5 July in Huntap Tondo. The analysis used the Wilcoxon signed rank test. Results showed that the knowledge of young women with a mean pretest value of 9.6 and a mean posttest value of 17.3 (p = 0.000 <0.05). The attitude of young women with a mean pretest value of 20.8 and a mean posttest value of 35.7 (p = 0.000 <0.05). Conclusion There is an effect of health education on the knowledge and attitudes of young women about early detection of breast cancer through Breast Self-Examination. It is expected that young women in the Huntap Tondo area will continue to improve their knowledge and attitudes toward preventing breast cancer by participating in counseling and being active in youth Posyandu activities.